Traumatic injuries to the renal blood vessels and in-hospital renal complications in patients with penetrating or blunt trauma - Alzerwi, Nasser A. N. (Frontiers in Surgery, 2023)
Background Traumatic injuries to renal blood vessels (IRBV) can have significant consequences for patients, impacting their mortality, morbidity, and quality of life. Objective This study aimed to compare trauma types and injury characteristics, vital signs, and outcomes in patients with and without IRBV (nIRBV) and examine whether IRBV and pre-existing renal dysfunction affected the likelihood of in-hospital renal complications (iHRC). Materials and Methods After identifying penetrating and blunt trauma victims with IRBV in the National Trauma Data Bank, patient demographics, injury-related variables, treatment outcomes, and deaths under care were analyzed and compared. Results Of the 994,184 trauma victims, 610 (0.6%) experienced IRBV. Victims in the IRBV group (IRBVG) had a significantly higher frequency of penetrating injuries (19.5% vs. 9.2%, P < 0.001) and higher injury severity score (ISS ≥25, 61.5% vs. 6.7%). Most injuries in both groups were unintentional, although a higher frequency of assault was noted in the IRBVG. The incidence of iHRC was higher in the IRBVG (6.6%) than in the nIRBVG (0.4%; P < 0.001). The IRBV OR = 3.5 [95% CI = (2.4–5.0)], preexisting renal disorders OR = 2.5 [95% CI = (2.1–2.9)], and in-hospital cardiac arrest OR = 8.6 [95% CI = (7.7–9.5)] were found to be among the factors associated with a higher risk of iHRC. Conclusions IRBV and pre-existing renal disorders considerably increased the risk of developing iHRC. Due to the long- and short-term consequences of associated cardiovascular, renal, and hemodynamic complications, victims of IRBV require specialized renal management and close monitoring.